A patient-based medaka alg2 mutant as a model for hypo-N-glycosylation - Jakab, Sevinç; Sakson, Roman; Hoffmann, Marcus; Grote, Valerian; Becker, Clara; Pakari, Kaisa; Beedgen, Lars; Thiel, Christian; Rapp, Erdmann; Ruppert, Thomas; Thumberger, Thomas; Wittbrodt, Joachim (Development, 2021)
Defects in the evolutionarily conserved protein-glycosylation machinery during embryonic development are often fatal. Consequently, congenital disorders of glycosylation (CDG) in human are rare. We modelled a putative hypomorphic mutation described in an alpha-1,3/1,6-mannosyltransferase (ALG2) index patient (ALG2-CDG) to address the developmental consequences in the teleost medaka (Oryzias latipes). We observed specific, multisystemic, late-onset phenotypes, closely resembling the patient's syndrome, prominently in the facial skeleton and in neuronal tissue.
Gesehen am 25.06.2021